TEACHERS’ STRATEGIES IN TEACHING ENGLISH TO GRADE X STUDENTS AT MAN 2 KOTA PALU - Nurfadillah, Andi; M. Said, Mawardin; Mashuri (Tadulako University, 2023)
The purpose of this research are two folds: to find out the teaching strategies used by the English teacher at MAN 2 Kota Palu, and to identify the reasons of implementing the strategies in the classroom. This research used qualitative research design. The participant of this research were two English teacher. In collecting the data, the instrument used were observation and interview . the data analyzed by using descriptive analysis. The findings showed that there were some teaching strategies used by the teachers in teaching English. The strategies used by the teacher in teaching English were: (1) the use of video like writing recount text and favorite song (by relying on learning topic), (2) reading text book, (3) translation (by looking up dictionary), and (4) asking question. The main reason reason of implementing teaching strategies was, they wanted to make the students active in the class. The basic consideration as an active facilitator in choosing the teaching strategies was to make classroom atmosphere that can make the students interact freely with each other in achieving learning goals.